Fundamentalism in Indonesian Political History: A Biography of Isa Anshary - Yusril Fahmi Adam; Imas Emalia (Buletin Al-Turas, 2022)
PurposeThis study aimed to uncover Muslem scholar and politician, Isa Anshary’s thought and practices of the fundamentalism in political actitivies that were not in Indonesian Islamic historiography. MethodThis qualitative study used a library research design which depended on the primary data of written literature or archives related to the research problem. The researchers read the data sources carefully to identify Isa Anshory’s thougth and practices of fundamentalism. The collected information were verified to unveal his thougth, ideas or pracices of fundamentalism in political activities. Results/FindingsThe study identified that Isa Anshary was a figure belonging to the fundamentalism group. His fundamentalism was a result of the strong influence of Al-Afghani, Abduh, Ridla and A Hassan. These various influences had become a stimulus for Isa Anshary to voice Islamic ideology and show a tough attitude in politics. ConclusionThis study concluded that Isa Anshary's fundamentalism in politics was a response to the post-independence political situation which was considered unsettled and aimed to protect the Islamic faith from the threat of secularism and communism